2005
DOI: 10.1115/1.2222375
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Study of the Hydraulically Expanded Tube-to-Tubesheet Joint

Abstract: A three-dimensional parametrized finite element model is established for the nonlinear analysis of the hydraulically expanded tube-to-tubesheet joint. Distribution of the residual contact pressure on the contact surface between the tube and the tubesheet is investigated. It is found that sealing circular bands exist on the contact surface which enhance the sealing of the joint since the residual contact pressures on the sealing circular bands are higher than on other positions. The sealing circular bands are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…At present, when the software ANSYS is used for the design of pressure vessels, it is suggested that the solid element should be used when the capability of computer and condition is appropriate, so as to simulate the actual situation much better and lead to a credible result [2]. Once the solid element is used in modeling, the meshing is an important link and it will influence the accuracy and scale of calculation directly [3]. There are lots of problems should be taken into consideration while meshing [4], such as 1) when solid element is used to simulate lamella structure, 4 layers of linear elements or 2 layers of quadratic elements should be existed in the direction of thickness; 2) For the model with no experience, basic mesh model and double mesh density model should be considered when checking the rationality of the size of mesh.…”
Section: Introductionmentioning
confidence: 99%
“…At present, when the software ANSYS is used for the design of pressure vessels, it is suggested that the solid element should be used when the capability of computer and condition is appropriate, so as to simulate the actual situation much better and lead to a credible result [2]. Once the solid element is used in modeling, the meshing is an important link and it will influence the accuracy and scale of calculation directly [3]. There are lots of problems should be taken into consideration while meshing [4], such as 1) when solid element is used to simulate lamella structure, 4 layers of linear elements or 2 layers of quadratic elements should be existed in the direction of thickness; 2) For the model with no experience, basic mesh model and double mesh density model should be considered when checking the rationality of the size of mesh.…”
Section: Introductionmentioning
confidence: 99%